Factors influencing supplier performance: Evidence from farmers in West Java, Indonesia - Fitri Aprilianty; Atik Aprianingsih; Mustika Sufiati Purwanegara (International Journal of Supply Chain Management, 2018)
AbstractThe purpose of this study is to investigate factors that may affect farmers performance in the buyer-seller relationship within the agribusiness supply chain. Those factors include benevolence, structural formalization and contract completeness, dependency, and power. The author investigates how the five variables may impact cooperativeness and performance. The respondents for this study are a hundred farmers from Cianjur, Gunung Halu, and Garut. The primary data then analyzed using descriptive statistics and path analysis. The results show that dependency influence performance through power and cooperativeness, meanwhile benevolence influences performance through cooperativeness.